Effect of Different Media on the Determination of the Number of Microorganisms in Frozen Prawns (Shrimp) - Rajagopal, M V (Fishery Technology, 1965)
Effect of Different Media on the Determination of the Number of Microorganisms in Frozen Prawns (Shrimp)